Effect of Sn interlayer on mechanical properties and microstructure in Al/Mg friction stir lap welding with different rotational speeds. (8th July 2020) - Zheng, Bo; Zhao, Li; Lv, Qingquan; Wan, Ge; Cai, Da; Dong, Shijie; Hu, Xinbin
Abstract: The effect of Sn foil layers on the mechanical properties and microstructure of friction stir lap welded 5052 aluminium alloy and AZ31B magnesium alloy was explored in this study. Models of numerous joints were set by different rotational (700, 900, 1100, 1300 and 1500 rpm) and welding speeds (50 mm min −1 ). Mg/Al dissimilar lap joints with and without Sn interlayer were produced by friction stir lap welding. The results suggest that Mg2 Sn intermetallic compounds formed instead of Mg17 Al12 and Mg2 Al3 intermetallic compounds. In direct welding, the joint are only connected by metallurgical bonding between atoms (Mg/Al). In solder joints with Sn interlayer, the joint is connected by the combined effect of metallurgical bonding between atoms (Mg/Sn, Al/Sn) and interface mechanical coupling. For the joint with Sn interlayer, the maximum fracture load of the joint with the Sn interlayer reached 3.72 kN at a rotational speed of 900 rpm. As the rotational speed is increased from 1300 rpm to 1500 rpm, the Sn content on the the advancing side and the retreating side is more, resulting in more Mg2 Sn crystal content, increased crack content. The joint performance gradually decreases. For the joint without a Sn interlayer, the microscopic morphology was a river-like pattern, which was characterized by brittle fracture. For a joint with a Sn interlayer, the microscopic morphology contained micro-dimples and a small quantity of inclusions, which were characterized by mixed fracture.